(untitled) (Journal of the Sociology and Theory of Religion, 2026)
This article explains why the Israeli Army—despite Israel’s economic strength and material superiority—struggles to translate battlefield success into decisive victory, in stark contrast to 1967. The core claim is institutional: over the past decades a welfare-state political economy, the diffusion of real power to unelected legal-bureaucratic actors, and the internalization of expansive “international norms” (notably proportionality as understood by military lawyers) have reshaped incentives, leadership selection, and rules of engagement in ways that privilege risk-averse legality over victory. The paper concludes with suggestion of reforms to re-center victory on territorial defeat and replacement of hostile regimes/social infrastructures, to re-scope military law and enforcement. The paper also suggests to reconsider attitude to hostages and reduce dependence on foreign actors.